The recently discovered Principe Scops-owl is highly threatened: distribution, habitat associations, and population estimates - Freitas, Bárbara (2022)
Species baseline information is required for effective biodiversity conservation. Here we provide sound ecological data to support effective conservation of the Principe Scops-owl, Otus bikegila Melo, Freitas, Verbelen, Costa, Pereira, Fuchs, Sangster, Correia, de Lima & Crottini 2022, discovered in 2016. We mapped the observed and potential distribution, inferred habitat associations, estimated population size, and assessed the International Union for Conservation of Nature (IUCN) Red List category for this species. Surveys were carried out across Príncipe Island during the long and short dry seasons, recording owl presence in sampling points along transects. These data were used to model distribution, revealing that the Principe Scops-owl is restricted to 34.4 km2 in the south of the island, inside the Príncipe Obô Natural Park. Most records were in lower altitude native forest. Remoteness was the most important variable to explain presence at island level, followed by land use, which showed that the species is restricted to forest, clearly depending on native forest. Distance sampling using different models suggested a population density ranging between 33.4 individuals/km2 (95% CI: 23.6–47.2) and 46.4 individuals/km2 (95% CI: 29.3–73.6), which extrapolates to an estimated population size ranging from 1,149 individuals (95% CI: 813–1,623) to 1,597 individuals (95% CI: 1,007–2,533). We propose that the species is classified as “Critically Endangered” due to the small extent of occurrence, coupled with occurrence in a single location and inferred continuing declines in the extent of occurrence, area of occupancy, number of mature individuals and area, extent, and quality of habitat. Effective conservation of the Principe Scops-owl requires regular monitoring and further studies focusing on reproduction and potential nest predation by introduced mammals. Widespread support for the conservation of the Natural Park is vital to ensure the protection of this species and the endemic-rich native forests of Príncipe on which it depends.